2013
DOI: 10.1111/jsr.12023
|View full text |Cite
|
Sign up to set email alerts
|

Accurate scoring of the apnea–hypopnea index using a simple non‐contact breathing sensor

Abstract: Summary Sleep apnea is a serious condition that afflicts many individuals and is associated with serious health complications. Polysomnography, the gold standard for assessing and diagnosing sleep apnea, uses breathing sensors that are intrusive and can disrupt the patient’s sleep during the overnight testing. We investigated the use of breathing signals derived from non-contact force sensors (i.e. load cells) placed under the supports of the bed as an alternative to traditional polysomnography breathing senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…force sensors) placed under the supports of a bed have been shown to have great utility for non-contact detection of various aspects of sleep while an individual lies on the bed. In our lab, we have used load cells to detect lying position [6], distinguish between sleep and wake [7], and have even utilized load cell data to detect sleep apnea[8, 9]. Load cells have also been shown to be able to detect breathing [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…force sensors) placed under the supports of a bed have been shown to have great utility for non-contact detection of various aspects of sleep while an individual lies on the bed. In our lab, we have used load cells to detect lying position [6], distinguish between sleep and wake [7], and have even utilized load cell data to detect sleep apnea[8, 9]. Load cells have also been shown to be able to detect breathing [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…BEATTIE et al [78] demonstrated the feasibility of using unobtrusive load cells installed under the bed to measure AHI. Calibrated cells can even be used to monitor a patient's weight as well as the lying position of an individual.…”
Section: Mattress Sensor Technologymentioning
confidence: 99%
“…Chen et al cited reducing computational complexity as a main driver towards a single signal [32]. Recently, multisensor systems have once again gained traction, generally with between 4 to 6, but sometimes up to 30 sensors [34][35][36][37][38][39][40][41][42]. Kortelainen et al originally embedded 160 sensors in a bed [40], but later reduced the number of sensors to just eight [43].…”
Section: Problem Statementmentioning
confidence: 99%
“…When the goal is to produce information from a group of signals, fusion can occur at a variety of points in the process: data-level, feature-level, and/or decision-level [113]. features using a Bayesian classifier [34,42]. Respiratory rates may also be extracted in the same manner.…”
Section: Fusion Levelsmentioning
confidence: 99%
See 1 more Smart Citation